Project work: Opportunity for young adults and pre-service teachers to develop intrapersonal and interpersonal intelligences. (2022)
Intrapersonal and interpersonal intelligence are two fundamental aspects for humans to start building social and academic relations within a learning environment. In addition, these two intelligences help to identify the different emotions such as fearness, anxiety, and insecurity among others that arise in an everyday English class that influences the perceptions of pre-service teachers and Young adults. This article evidences how through a project work and the guidance of one of the pre-service teachers that were also one of the researchers, the pre-service teachers (12 participants) and young adults from Universidad Católica Luis Amigó from the city of Medellín (16 participants) were able to work and construct confidence in themselves and in others. Also, the analysis of the data collected in the research shows that pre-service teachers and young adults are able to work on their self-validation and explore their inner potential to build their sociability through project work application.